2013
DOI: 10.5194/bg-10-5267-2013
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of growth rate and mortality with size and its consequence on size spectra of natural microphytoplankton assemblages in the East China Sea

Abstract: Allometric scaling of body size versus growth rate and mortality has been suggested to be a universal macroecological pattern, as described by the metabolic theory of ecology (MTE). However, whether such scaling generally holds in natural assemblages remains debated. Here, we test the hypothesis that the size-specific growth rate and grazing mortality scale with the body size with an exponent of −1/4 after temperature correction, as MTE predicts. To do so, we couple a dilution experiment with the FlowCAM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…First, it is now clear that heterotrophic protists (in particular dinoflagellates) are important consumers of large cells such as diatoms (Calbet 2008, Sherr & Sherr 2009. Second, although some studies have found that the smallest phytoplankton (picocyanobacteria and picoeukaryotes) do suffer higher grazing losses than larger cells (Latasa et al 1997, Landry et al 2000, Strom et al 2007, others have reported similar grazing pressure on phytoplankton groups of markedly different mean cell size (Latasa et al 2005, Gutiérrez-Rodríguez et al 2011, Teixeira et al 2011, Chang et al 2013. In addition, global analyses of grazing rate by microzooplankton, which collectively consume most of the phytoplankton daily production, indicate that losses to predation are of the same magnitude (approximately 60-70% of daily primary production) in regions that are known to have widely contrasting phytoplankton size structure (Calbet & Landry 2004, Schmoker et al 2013.…”
Section: Why Are Blooms Not Dominated By Small Cells?mentioning
confidence: 99%
“…First, it is now clear that heterotrophic protists (in particular dinoflagellates) are important consumers of large cells such as diatoms (Calbet 2008, Sherr & Sherr 2009. Second, although some studies have found that the smallest phytoplankton (picocyanobacteria and picoeukaryotes) do suffer higher grazing losses than larger cells (Latasa et al 1997, Landry et al 2000, Strom et al 2007, others have reported similar grazing pressure on phytoplankton groups of markedly different mean cell size (Latasa et al 2005, Gutiérrez-Rodríguez et al 2011, Teixeira et al 2011, Chang et al 2013. In addition, global analyses of grazing rate by microzooplankton, which collectively consume most of the phytoplankton daily production, indicate that losses to predation are of the same magnitude (approximately 60-70% of daily primary production) in regions that are known to have widely contrasting phytoplankton size structure (Calbet & Landry 2004, Schmoker et al 2013.…”
Section: Why Are Blooms Not Dominated By Small Cells?mentioning
confidence: 99%
“…The decoupling between growth and mortality may be the result of non-steady-state conditions due to physical forcing and food web complexity, which makes it difficult to predict the grazing mortality at global scales. Chang et al (2013) assumed that allometric scaling of phytoplankton cell size of natural assemblage to growth and mortality could be described by the metabolic theory of ecology (MTE). While their experiments in the ECS did not support the MTE, they suggested that the higher grazing impacts of large phytoplankton cells release the grazing mortality of small phytoplankton cells.…”
Section: Continental Margin Biota and Their Ecological Characteristicsmentioning
confidence: 99%
“…Metazoans connect grazing and microbial food webs through their feeding on phytoplankton and protozoans (e.g., Kobari et al, 2003), suggesting that metazoan growth is an integration of production at lower trophic levels. Similarly to Chang et al (2013), tested the MTE for a copepod community in the ECS. The results from their experiments generally agreed with the MTE because growth rates of the copepod community showed positive correlations with ambient temperature and negative to their body size.…”
Section: Continental Margin Biota and Their Ecological Characteristicsmentioning
confidence: 99%
“…Metazoans connect grazing and microbial food webs through their feeding on phytoplankton and protozoans (e.g., Kobari et al, 2003), suggesting that metazoan growth is an integration of production at lower trophic levels. Similarly to Chang et al (2013), tested the MTE for a copepod community in the ECS. The results from their experiments generally agreed with the MTE because growth rates of the copepod com-munity showed positive correlations with ambient temperature and negative to their body size.…”
Section: Continental Margin Biota and Their Ecological Characteristicsmentioning
confidence: 99%